In vitro biomechanical comparison of a newly designed interlocking nail system to a standard DCP - Brückner, M.; Unger, M.; Spies, M. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2014)
Objective: To describe a newly designed interlocking nail system (Targon® Vet System, TVS) tested in a model of diaphyseal femoral fractures in cats. Material and methods: Introduction of the TVS and presentation of the system components. Evaluation of application range and biomechanical testing of the TVS in cadaver bones under cyclic loading until fatigue failure occurred. The first two test groups compared the influence of implantation and immediate removal of the TVS locking bolts and six holes created by 2.0 mm cortical screws on the stability of feline femora. In the third group the two fixation systems were compared to each other with implants in place in an osteotomy gap model. The failure mode was statistically compared for each group (p < 0.05). Results: Femora after implantation and removal of the bolts of the TVS were significantly stiffer than after implantation and removal of the six 2.0 mm cortical screws. In the osteotomy gap model, femora with the TVS in place failed somewhat later, but not statistically significant, than the opposite femur of the same cat with the 2.0 8-hole DCP in place. Conclusion and clinical relevance: Using this testing method, stability of the TVS seems to be biomechanically comparable to conventional osteosynthesis plate systems. Therefore the TVS may be an encouraging alternative to conventional osteosynthesis systems in diaphyseal fractures, offering several advantages without the need for extensive specialized equipment.
Keywords: Interlocking nail; cat; femur; diaphyseal fractures